Morphological perspectives : papers in honour of Greville G. Corbett - Corbett, Greville G.; Baerman, Matthew; Bond, Oliver; Hippisley, Andrew (Edinburgh University Press, 2019)
Morphological Perspectives takes words as the starting point for any questions about linguistic structure: their form, their internal structure, their paradigmatic extensions, and their role in expressing and manipulating syntactic configurations.